2017
DOI: 10.1038/nature24266
|View full text |Cite
|
Sign up to set email alerts
|

History-independent cyclic response of nanotwinned metals

Abstract: Nearly 90 per cent of service failures of metallic components and structures are caused by fatigue at cyclic stress amplitudes much lower than the tensile strength of the materials involved. Metals typically suffer from large amounts of cumulative, irreversible damage to microstructure during cyclic deformation, leading to cyclic responses that are unstable (hardening or softening) and history-dependent. Existing rules for fatigue life prediction, such as the linear cumulative damage rule, cannot account for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(82 citation statements)
references
References 46 publications
1
81
0
Order By: Relevance
“…Metallic materials with a high tensile strength might have a low-fatigue lifetime. However, the nanotwinned Cu films have been demonstrated to have high-fatigue resistance [8]. In addition, Li et al also reported nanotwinned Cu redistribution lines possess high-fatigue resistance to temperature cycling tests [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallic materials with a high tensile strength might have a low-fatigue lifetime. However, the nanotwinned Cu films have been demonstrated to have high-fatigue resistance [8]. In addition, Li et al also reported nanotwinned Cu redistribution lines possess high-fatigue resistance to temperature cycling tests [20].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, nanotwinned copper (nt-Cu) was found to have high strength, ideal ductility, excellent thermal stability, low resistivity [4,5], high electromigration resistance [6], and history-independent cyclic response during fatigue tests [7,8]. Generally, magnetron sputtering and electroplating have been applied in fabricating highly <111>-oriented nt-Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to the similar size and uniform distribution of α phase, FLM with nanoscale α phase possesses super resistance against fatigue crack initiation than BM. Moreover, Pan et al [36] has found that the dislocations move collectively back and forth along the nanotwins during cyclic loading, which indicated that nanotwins promotes the reversible dislocation slip and increases the fatigue life. Whereas, cyclic plastic deformation is produced at each cycle during low cycle fatigue.…”
Section: Cracks Propagationmentioning
confidence: 99%
“…As the extension of stacking faults, twin activities are highly related to partial dislocation activities. Moreover, studies revealed that the induced twins can enhance mechanical performances such as strength 88,89 , hardness 90,91 , fracture toughness 88,89 and anti-fatigue 92 .…”
Section: And Twins and Grain Boundariesmentioning
confidence: 99%
“…However, in-situ TEM observation studies by Wang et al 94,95 revealed that full dislocation activities are still existent in the deformation processes of nc-Pt thin films, even in the d~10nm Pt grains. Figure 2.1 are high-resolution (HR) TEM images that show the full dislocations nucleation and annihilation processes during the tensile deformation processes 92 . Grain A (d~12 nm) was monitored during the whole deformation processes, as labelled by white dash lines in Figure 2.1a.…”
Section: Dislocation-mediated and Twinning Mechanismsmentioning
confidence: 99%